Gender Differences in Perceptions of Grandchildren towards Grandparent Nurturing - Muhammed Yusuf; Mohammed Y. M. Mai; Maria Salih (International Review of Management and Marketing, 2016)
Persisting writing on grandparents' enthusiasm towards grandchildren's development shows that numerous grandparents take part in raising their grandchildren at a young age and preparing them for a better future. Grandparents motivate their grandchildren to excel scholastically and morally. The present study investigates grandchildren's perceptions towards their grandparents' nurturing educationally, culturally, socially, and religiously. One hundred and eighty one grandchildren from two Malaysia cities voluntarily responded to the parent-grandparent as educator questionnaire - children version. The cities are Ipoh and Tanjung Malim which were situated in Perak state. An independent t-test was used to answer the research Question: Is there any significant difference between perceptions of grandchildren towards grandparents' nurturing according to the gender of the respondents? The results of the independent t-test show that there were no statistically significant differences in the scores of the male and female on their perceptions towards grandparents' upbringing educationally, culturally, socially, and religiously. These results suggest that both male and female were equally encouraged by their respective grandparents to perform well academically, to value culture, to involve in social activities, and to be religious by good practices.